LEGAL PROTECTION FOR INSURANCE COMPANIES AGAINST ABUSE OF INSURANCE CLAIMS - Candra, Dimas; Djajaputra, Gunawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Uncertainty in human life gives rise to the need for legal and economic protection instruments, one of which is through the insurance mechanism. As a form of risk transfer, insurance provides compensation guarantees for losses due to uncertain events, such as accidents, fires, or death. In the legal framework in Indonesia, the relationship between the insurer and the insured is formed through an agreement (policy) or normative provisions in laws and regulations. However, in practice, this relationship is inseparable from the problem of moral hazard, especially the misuse of claims by the insured who act dishonestly. This phenomenon not only causes economic losses for insurance companies, but also threatens the integrity of the insurance system itself. Therefore, an effective legal protection mechanism is needed for insurance companies to deal with these manipulative practices. This paper examines the forms of legal protection available, both through contractual instruments (internal) and external regulations such as Law Number 40 of 2014 concerning Insurance. With a normative legal approach, this paper aims to provide a deeper understanding of the importance of maintaining a balance of rights and obligations in insurance contracts and the need to strengthen legal aspects in anticipating misuse of claims.